Stress-strain analysis of trochanteric fracture models by Evans type 2 after total hip replacement - Babalyan, Vladimir; Karpinsky, Mykhaylo; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
A proximal femoral fracture in elderly and senile age is complex medical and social problem. Author’s method of treatment includes cemented bipolar hemiarthroplasty with augmentation, K-wires and/or sterclage fixation. Frequent complication of intramedullary nailing is femoral head damage (cut-off, cut-out), so-there is need to make hip arthroplasty. Author’s device allows to change intramedullary nailing to arthroplasty without changing of femoral stem and with the same instruments. Objective: to work out the mathematic model of throchanteric fractures according to Evans classification and to study the main areas of stresses in the proximal femoral part at arthroplasy and additional K-wires fixation. Methods: mathematic femur models with throhanteric fractures of different types by Evans were worked out. Fractures type 2 were fixed with standard and modular endoprothesis. We studied stress-strain condition under the vertical compressive loading. Results: at arthroplasty the highest level of stresses were observed in the upper (100,8 МPа) and lower (90,9 МPа) parts of endoprothesis neck, but bone stresses were low (2,2–10,7 МPа). Application of modular system the maximum stresses (92,4 МPа) were appeared on the lateral side of the femur around the distal end of the loading rod, on the lower part of femoral neck (71,8 МPа) and in the fracture area (71,3 МPа). Conclusions: modular system allows decreasing of stresses significantly in all control points of bone elements. Areas of high tensions appear in the place of junction of loading rod with intramedullar. They exceed indicators of model with endoprothesis.